MIRERC 060/2025: Leveraging Community Health Workers for the Promotion of Breast Cancer Awareness and Timely Help-Seeking Behaviour (BreCATH-B study), Among Underserved Rural Population in Kenya: A Protocol for a Hybrid Type II Cluster Randomised Controlled Trial. - Kailemia, PhD, Dr Peter N. (MUST Institutional Research Ethics Review Committee (MIRERC), 2025)
CLINICAL TRIAL SYNOPSIS OVERALL GOAL: The overarching Aim of the BreCATH-B program is to co-create, implement, and evaluate a theoretically informed, evidence-based, and culturally-sensitive breast screening program that enables earlier diagnosis and reduces advanced-stage diagnosis in an underserved rural population in Kenya. To accomplish this goal, the project will be guided by several Specific Aims. Specific Aim 1: Describe contextual facilitators and barriers to the implementation of the BreCATH-B program from the perspectives of patient partners and stakeholders. This aim will use mixed methods to explore implementation determinants using the PRISM framework. Specific Aim 2: Co-create the BreCATH-B program by adapting an existing evidence-based intervention (EBI) that has been developed and evaluated in Rwanda through a randomised controlled trial. This aim will draw on the results of Aim1 to tailor the breast cancer Early Diagnosis intervention by Pace and colleagues focusing on awareness, clinical breast exams and improving the referral system. Specific Aim 3: Co-create an implementation package and tailoring implementation strategies to the Kenyan context to improve intervention-context fit. This aim builds on the results of Specific Aims 1 and 2 and involves the co-creation of a training package to enhance the knowledge of Community Health Workers and primary healthcare workers on risk factors, symptoms of female breast cancer, the importance of seeking timely medical evaluation for breast concerns and reducing local barriers to accessing breast health care. Primary healthcare workers will further be trained on the performance of clinical breast examinations. This aim further involves the collaborative creation and tailoring of implementation strategies considering the local implementation determinants. Specific Aim 4: Evaluate the effectiveness of the BreCATH-B program by assessing its impact on the level of breast cancer awareness, level of utilization of clinical breast examination, length of patient and primary care intervals and number of referrals. The aim focuses on evaluating the intervention’s primary and secondary outcomes arising from the implementation of the intervention highlighted in Specific Aim 3. Specific Aim 5: Describe the implementation process and degree to which the BreCATH-B program was successfully implemented, with a focus on its reach, effectiveness, adoption, implementation, and maintenance (RE-AIM domains), including health equity outcomes. Specific Aim 6: Conduct an economic evaluation of implementation strategies for the BreCATH-B program. The aim seeks to evaluate the cost of implementation strategies across the phases of intervention implementation from a provider’s perspective.